This study stems from an artistic phenomenon that has its traces in a poetic function which observes the milestone of creation in employing in employing the Qur’anic intertextuality in the poetry of Ashja 'al-Salami. Intertextuality is a met - Rashid , Mayada (Islamic Sciences Journal, 2023)
ABSTRACT This study stems from an artistic phenomenon that has its traces in a poetic function which observes the milestone of creation in employing in employing the Qur’anic intertextuality in the poetry of Ashja 'al-Salami. Intertextuality is a method of modern studies suitable for poets' poetry in employing the technicality of origins and belongings to supplement their texts with anew power , especially the use of the Qur’an, literature in an artistic way that increases the indications and richness of the poetic text, and opens wide horizons for contemplation and interpretation)) especially, when this artistic creativity is from a creative poet with his religious outcome. Intertextuality is based on previous texts absent in the poet’s memory, and nothing is more beautiful and deeper than employing the heritage of religious culture and Qur’anic texts that have a prominent effect on deepening the meaning and enriching the text artistically and intellectually. The research relied on the descriptive and analytical approach in tracking, monitoring, describing and analyzing the phenomenon of intertextuality. The poet Ashjae Alsalmi, like the other poets, he drew a lot from the meanings of the Noble Qur’an and its vocabulary, for he does not cease to refer to the Qur’anic text and the religious heritage which are entrenched in himself, to obtain what nourishes and benefits his poetry, and to highlight the effectiveness of intertextuality in showing the dimensions of poetic experience. The concept of intertextuality is a broad and comprehensive concept, as it accommodates various forms of textual interaction, therefore it is not subject to retraction and reduction in any form All poets used it in their poems and excelled in their handling of it, whether in direct or indirect intertextuality with the words of the Noble Qur’an and its meanings, and among them the poet of Ashjae Alsalmi who is the topic of this research.